Morbillivirus infection in cetaceans stranded along the Italian coastline: pathological, immunhistochemical and biomolecular studies. - Di Guardo G.; Di Francesco C. E.; Eleni C.; Cocumelli C.; Scholl F.; Casalone C.; Peletto S.; Mignone W.; Tittarelli C.; Di Nocera F.; Fernandez A.; Marcer F.; et al. (2012)
Following the two Dolphin Morbillivirus (DMV) epidemics occurred in 1990-’92 and in 2006-2008 among Mediterranean Sea striped dolphins (Stenella coeruleoalba), a number of morbilliviral infection (MI) cases with peculiar features were reported in striped dolphins found stranded along the Spanish coastline. Affected cetaceans showed a subacute-to-chronic, non-suppurative encephalitis, with brain lesions strongly resembling those found in the course of human “subacute sclerosing panencephalitis” and “old dog encephalitis”. Interestingly, brain was the only tissue in which morbilliviral antigen and/or genome could be detected in these dolphins. Beside the peculiar case of morbilliviral encephalitis described in a young striped dolphin found beached in 2009 along the Latium sea coast of Italy, we observed 5 additional MI cases in 2 striped dolphins, 1 bottlenose dolphin (Tursiops truncatus) and 2 fin whales (Balaenoptera physalus), all of which found stranded in 2011 along the Italian coastline. Noteworthy, 3 out of these cetaceans (2 striped dolphins and 1 bottlenose dolphin) showed immunohistochemical (IHC) and/or biomolecular (PCR) evidence of morbilliviral antigen and/or genome exclusively in their brain, with 1 striped dolphin and 1 bottlenose dolphin also exhibiting a non-suppurative encephalitis. Furthermore, simultaneous IHC and PCR evidence of a Toxoplasma gondii coinfection was found in 1 stranded fin whale. In conclusion, the above results are strongly reminiscent of those reported in striped dolphins after the two MI epidemics occurred in 1990-‘92 and in 2006-2008, with evidence of morbilliviral antigen and/or genome being found exclusively in the brain tissue from affected animals.